The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/2014ja020371
|View full text |Cite
|
Sign up to set email alerts
|

Modeling subauroral polarization streams during the 17 March 2013 storm

Abstract: The subauroral polarization streams (SAPS) are one of the most important features in representing magnetosphere-ionosphere coupling processes. In this study, we use a state-of-the-art modeling framework that couples an inner magnetospheric ring current model RAM-SCB with a global MHD model Block-Adaptive Tree Solar-wind Roe Upwind Scheme (BATS-R-US) and an ionospheric potential solver to study the SAPS that occurred during the 17 March 2013 storm event as well as to assess the modeling capability. Both ionosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 46 publications
3
71
1
2
Order By: Relevance
“…showed that they were directly linked to the partial ring current localized pressure peak, and other observations and numerical modeling has confirmed and further quantified this relationship (e.g. Garner et al 2004;Mishin and Burke 2005;Yu et al 2015;Yuan et al 2016;Califf et al 2016). SAPS are relatively stable during storms, being a persistent feature across the evening sector that can last for many hours (e.g.…”
Section: Ring Current and Ionosphere And Thermospherementioning
confidence: 67%
“…showed that they were directly linked to the partial ring current localized pressure peak, and other observations and numerical modeling has confirmed and further quantified this relationship (e.g. Garner et al 2004;Mishin and Burke 2005;Yu et al 2015;Yuan et al 2016;Califf et al 2016). SAPS are relatively stable during storms, being a persistent feature across the evening sector that can last for many hours (e.g.…”
Section: Ring Current and Ionosphere And Thermospherementioning
confidence: 67%
“…Through a comparison with the modeling by the Rice Convection Model, Clausen et al () found a good agreement between the longitudinal distribution of the plasma pressure gradients in the RC and the SAPS variation with MLT. Other global simulation work (e.g., Goldstein et al, ; Wang, Lühr, & Ma, ; Yu et al, ; Zheng et al, ) also demonstrated that the subauroral plasma flow was a direct manifestation of the distributions of the RC and ionospheric conductivity, especially during magnetically disturbed periods.…”
Section: Introductionmentioning
confidence: 89%
“…We next explore the subauroral events detected by the Van Allen Probes during first hours of the St. Patrick's day 2013 and 2015 major storms. On 17 March 2013, the arrival of a solar wind shock initiated a sequence of substorms driven by solar wind pressure pulses and oscillations of the IMF B Z [e.g., Yu et al ., , Figure 2; Foster et al ., ]. The first substorm, with two active phases starting at tnormaleo(1,1) 06:00 and tnormaleo(1,2) 06:35 UT, led to AE ≈1100 nT at ≈06:43 UT.…”
Section: Observationsmentioning
confidence: 99%